Morphologic and biometric evaluation of chick embryo eyes in ovo using 7 Tesla MRI - Tobias Lindner (Nature Portfolio, 2017)
Abstract The purposes of this study were (1) to characterize embryonic eye development during incubation in ovo and (2) to analyze the putative influence of repetitive ultrahigh-field MRI (UHF-MRI) measurements on this development. A population of 38 fertilized chicken eggs was divided into two sub-groups: two eggs (Group A) were examined repeatedly during the developmental period from embryonic day 1 (E1) to embryonic day 20 (E20) to evaluate the influence of daily MRI scanning. A second larger group of 36 eggs was examined pairwise on one day only, from E3 to E20, and the embryos were sacrificed immediately after MR imaging (Group B). Fast T2-weighted MR sequences provided biometric data on the eye with an in-plane resolution of 74 μm. The data show rapid growth of the eye with a steep increase in intraocular dimensions in all axis directions and in eyeball volume during initial development up to E10, followed by a phase of reduced growth rate in later developmental stages. Comparison of the two groups revealed no differences in ocular development.